Menguatkan Self-Efficacy untuk Meningkatkan Pemecahan Masalah Matematis: Studi Kualitatif pada Siswa Madrasah Ibtidaiyah - Fatik Lutviana Anggraini (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the relationship between self-efficacy and mathematical problem-solving ability among Madrasah Ibtidaiyah students. The research employed a qualitative approach and was conducted at Madrasah Ibtidaiyah Nurur Rahman Tamanan, Bondowoso Regency. The participants consisted of upper-grade Madrasah Ibtidaiyah students, with teachers involved as supporting informants. Data were collected through in-depth interviews, classroom observations during mathematics learning, and documentation of students’ written work. Data analysis was carried out thematically through data reduction, data display, and conclusion drawing, while data trustworthiness was ensured through source and technique triangulation. The findings indicate that self-efficacy plays a significant role in students’ mathematical problem-solving ability. Students with high self-efficacy tend to demonstrate greater confidence, persistence, and reflective thinking in understanding problems, planning solution strategies, and completing mathematical tasks. In contrast, students with low self-efficacy show hesitation, low persistence, and greater difficulty when facing mathematical problem-solving tasks. This study concludes that strengthening students’ self-efficacy is a crucial aspect in improving the quality of mathematics learning in Madrasah Ibtidaiyah